Gluten-Free Sweet Potato Flour: Effect of Drying Method and Variety on the Quality and Bioactivity - Nelson Pereira; Ana Cristina Ramos; Marco Alves; Vítor D. Alves; Cristina Roseiro; Manuela Vida; Margarida Moldão; Marta Abreu (Molecules)
Sweet potato (Ipomoea batatas (L.) Lam.) is a nutrient-dense crop rich in fibre, minerals, and antioxidant compounds, including carotenoids and phenolic compounds, such as anthocyanins. Dehydrating sweet potato (SP) for flour production enhances its value and produces shelf-stable, health-promoting food products. This study investigated the effects of hot-air drying (HAD: 75 °C/20 h) and freeze-drying (FD: −41–30 °C/70 h) on the bioactive composition of flours from three SP varieties: Bonita (white-fleshed), Bellevue (orange-fleshed), and NP1648 (purple-fleshed). Key assessments included the total phenolic content (TPC), the total carotenoid content (TCC), and the total anthocyanin content (TAC) and the antioxidant activity (DPPH and FRAP). The results revealed distinct raw materials’ bioactive profiles: Bellevue was rich in TCC (49.3 mg of β-carotene/100 g db), NP1648 showed elevated TAC (27.3 mg of cyanidin-3-glucoside/100 g db), and Bonita exhibited minimal content of bioactive compounds. Both drying methods yielded significant losses of bioactive compounds, with the TPC decreasing by over 60%, while TAC and TCC losses did not exceed 32%, revealing higher stability. Multivariate analysis indicated that the variety significantly influenced the bioactive profiles more than the drying method. The interaction between carotenoids and anthocyanins and the SP fibrous composition likely contributed to their stability during drying, indicating that FD showed no advantages over HAD. The appealing colours and high antioxidant content of Bellevue and NP1648 flours suggest their potential as ingredients for enhancing foods’ bioactivity and sensory acceptance.